Physico‐chemical, sensory, antioxidant and electromyographic analyses of functional liquid diets (IDDSI levels 0–2) formulated for dysphagia patients - Sodhi, Navdeep Singh; Dhillon, Bhavnita; Kaur, Ramneet; Goria, Gurleen; Sharma, Shivangi; Jaiswal, Sunanda (International journal of food science & technology, 2023)
Summary Dysphagia is a symptom that refers to difficulty during the progression of the alimentary bolus from the mouth to the stomach. This may lead to malnutrition and negative effects on quality of life. Doctors and dieticians around the globe are looking for nutritious texture‐modified diets which are easier to chew and swallow thus could reduce the risks associated with choking in dysphagia patients. In this study, different functional liquid diets were formulated under International Dysphagia Diet Standardization Initiative (IDDSI) levels 0–2. The diets were made with incorporation of various fruits and vegetables to enhance their nutritional profile. The formulated liquid diets were analysed for their proximate composition, colour, antioxidant and sensory properties. The formulated liquid diets were high in nutrients and antioxidants. Also, all the formulated products were highly acceptable based on various sensory attributes indicating their potential to be incorporated in the diet plan of dysphagia patients. Electromyography (EMG) study was conducted to acquire myoelectrical activities of both masseter and suprahyoid muscles during oral processing of liquid diets by human subjects. The acquired EMG oral processing parameters significantly (P < 0.05) correlated with ease of swallowing and IDDSI levels. Hence, EMG technique provides in vivo texture evaluation and real‐time swallowing patterns and thus can be an effective approach for the formulation of texture‐modified diets for dysphagia patients. Formulation of liquid diets, acquisition of electromyographic data and their correlations